Amplitude modulations of seasonal variability in the Karimata Strait throughflow - Nie, Yicong; Li, Shujiang; Wei, Zexun; Xu, Tengfei; Pan, Haidong; Nie, Xunwei; Zhu, Yaohua; Susanto, R. Dwi; Agustiadi, Teguh; Trenggono, Mukti (Frontiers in Marine Science, 2023)
The Karimata Strait (KS) throughflow between the South China Sea (SCS) and Java Sea plays essential role in heat and freshwater balance in the SCS and dual roles in strengthening/reducing the main Indonesian throughflow (ITF) in the Makassar Strait. A sustained long-term monitoring of ITF is logistically challenging and expensive; therefore, proxies are needed. Hence, in this paper we used a combination of in situ measurement of KS throughflow and satellite-derived sea surface height (SSH) and sea surface wind (SSW) to determine interannual and decadal modulations of seasonal KS throughflow associated with El Niño-Southern Oscillation (ENSO), Indian Ocean dipole (IOD), Pacific Decadal Oscillation (PDO). regression, correlation, harmonic and power spectrum analyses were used. The results show that there are significant interannual to decadal modulations in the seasonal amplitude of the KS throughflow. The modulation ranges of the volume and heat transports seasonal amplitudes are 1.36-1.92 Sv (1 Sv = 106 m3 s-1) and 126.41-173.36 TW (1 TW = 1012 W), respectively. Both have a significant cycle with a period of 9 years. From 1994 to 2020, the seasonal amplitude of volume transport through the KS shows a minor linear upward trend of 37.75 ± 15.69 mSv decade-1 (1 mSv = 103 m3 s-1). Meanwhile, the seasonal amplitude of the heat transport also increases, at a rate of 4.78 ± 1.52 TW decade-1. The KS volume transport is positively correlated with PDO and ENSO (r2 = 0.68 and r2 = 0.58), with lag times of 12 and 10 months, respectively. The results of composite analysis indicate that the interannual variability of the KS transport is related to the interannual anomalies of the SSH gradient and the local SSW fields in the boreal winter.